In Vivo Targeting and Positron Emission Tomography Imaging of Tumor Vasculature with (66)Ga-Labeled Nano-Graphene - Hong, Hao (2012)
The goal of this study was to employ nano-graphene for tumor targeting in an animal tumor model, and quantitatively evaluate the pharmacokinetics and tumor targeting efficacy through positron emission tomography (PET) imaging using (66)Ga as the radiolabel. Nano-graphene oxide (GO) sheets with covalently linked, amino group-terminated six-arm branched polyethylene glycol (PEG; 10 kDa) chains were conjugated to NOTA (1,4,7-triazacyclononane-1,4,7-triacetic acid, for (66)Ga-labeling) and TRC105 (an antibody that binds to CD105). Flow cytometry analyses, size measurements, and serum stability studies were performed to characterize the GO conjugates before in vivo investigations in 4T1 murine breast tumor-bearing mice, which were further validated by histology. TRC105-conjugated GO was specific for CD105 in cell culture. (66)Ga-NOTA-GO-TRC105 and (66)Ga-NOTA-GO exhibited excellent stability in complete mouse serum. In 4T1 tumor-bearing mice, these GO conjugates were primarily cleared through the hepatobiliary pathway. (66)Ga-NOTA-GO-TRC105 accumulated quickly in the 4T1 tumors and tumor uptake remained stable over time (3.8 ± 0.4, 4.5 ± 0.4, 5.8 ± 0.3, and 4.5 ± 0.4 %ID/g at 0.5, 3, 7, and 24 h post-injection respectively; n = 4). Blocking studies with unconjugated TRC105 confirmed CD105 specificity of (66)Ga-NOTA-GO-TRC105, which was corroborated by biodistribution and histology studies. Furthermore, histological examination revealed that targeting of NOTA-GO-TRC105 is tumor vasculature CD105 specific with little extravasation. Successful demonstration of in vivo tumor targeting with GO, along with the versatile chemistry of graphene-based nanomaterials, makes them suitable nanoplatforms for future biomedical research such as cancer theranostics.